How gender and child sensitive was the relief received after the tsunami? - Senanayake, M. P.; Ranawaka, Chinthana; Fernanado, Manisha (Sri Lanka college of pediatricians, 2011)
The status of women has a direct bearing on the condition of children. Countries where child mortality and morbidity are high rate low on how they treat women 1 . Disaster affected populations are also said to reflect a gender bias and such inequalities were reported following the tsunami of 2004, from Indonesia and India 2,3 . We assessed the gender impact of the post disaster health response and recovery process in a severely tsunami affected community in southern Sri Lanka. Method Pre and post disaster population structures were analysed. Focus group discussions with families attending a polyclinic set up in the immediate aftermath of the disaster and interview of key informants were utilized and the recovery process was assessed through a household survey carried out 14 months after the disaster and an interviewer __________________________________________ 1 Professor in Paediatrics, Department of Paediatrics, Faculty of Medicine, Colombo, 2 Pre-intern Medical Officer, 3 Volunteer General Practitioner, Australian Youth Ambassador Programme administered questionnaire was used to record responses. Results The village of Seenigama comprised a pre-disaster total population of 1448 persons. Recorded deaths totaled 120 with a profile of 60 adult women, 39 adult men and 21 children 4 . Almost all dwellings were damaged. Fourteen months after the disaster 412 families continued to live in this village. Majority of households attended a poly-clinic that was initiated by a local non-governmental organization and the Sri Lanka College of Paediatricians and clinic records were available for over 400 under 18 year olds. One hundred and twenty five randomly selected women consented to share their experiences of the relief received while in makeshift refugee camps and during the process of rebuilding their lives at home. Thirty nine respondents were from female headed households.
Keywords: Tsunami; relief, gender; child sensitive